2018
DOI: 10.26911/theijmed.2018.03.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Macro and Microvascular Complication in Type 2 Diabetes Mellitus Patients at Dr. Moewardi Hospital, Surakarta

Abstract: Background: Type 2 Diabetes Mellitus (Type 2 DM) is one of the major causes of morbidity and mortality worldwide. Morbidity and mortality due to diabetes are associated with the development of various microvascular complications (retinopathy, nephropathy, and neuropathy) and macrovascular complications (coronary heart disease, stroke, and peripheral vascular disease). This study aimed to examine the determinants of biopsychosocial macro and microvascular complications in patients with type 2 DM at Dr. Moewardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… 12 Development of microvascular and macrovascular complications cause significant morbidity and mortality among people with diabetes. 24 People with diabetes with uncontrolled blood glucose are at increased risk of developing these complications. 25 Achieving the goal of glycemic control is the most effective way to avoid or delay the occurrence of diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Development of microvascular and macrovascular complications cause significant morbidity and mortality among people with diabetes. 24 People with diabetes with uncontrolled blood glucose are at increased risk of developing these complications. 25 Achieving the goal of glycemic control is the most effective way to avoid or delay the occurrence of diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference with other studied parameters in mixed complications and control groups. Handoko et al [34] indicated that the length of sickness had an effect on the microvascular complications in T2DM patients. This was in accordance with a study conducted by Abu Al-Halaweh et al [35] who observed substantial link between microvascular problems and diabetes duration.…”
Section: Parametersmentioning
confidence: 99%
“…Early detection and treatment, on the other hand, reduce the incidence of ulceration. 5 Other macro-vascular complications like Coronary artery diseases (CAD) and cerebrovascular diseases like stroke are rapidly growing and strongly associated with DMT2 and 2-4 folds more common in DMT2 patients compared with those without diabetes. 6 According to the world health organization (WHO), the prevalence of CAD only in the Eastern Mediterranean region (EMRO) is 54% while these deaths may vary from 13% to 49% depending on the country also accounts for a considerable number of deaths in the region.…”
Section: Introductionmentioning
confidence: 99%